Psikoedukasi Mengenali dan Mengelola Emosi pada Siswa/i SMA: Psychoeducation on Recognizing and Managing Emotions in High School Students - Novianty, Anita; Paramita, Widia; Rachel, Kathleen (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Adolescence journey was known as storm and stress stage that led to serious effect towards adolescent’ psychological life. This community service was intended to understand the effectiveness of psychoeducation on understanding emotion and emotion management towards private high school students in Jakarta. The participants in this program were consisted of 22 students aged 15-18 years old. One group pre-post test design without controlled group was employed as the experiment design for emotion module in this program. Eleven likert items was used as instrument. Paired-samples t-test was used to analyze data. The result showed significantly difference with small effect size before and after psychoeducation. This indicated the increase of understanding regarding emotion, emotion expressions, as well as emotion management for high schoold students after psychoeducation.